Chloroanisoles occurrence in wine from grapes subjected to electrolyzed water treatments in the vineyard. (November 2020) - Gabrielli, Mario; Englezos, Vasileios; Rolle, Luca; Río Segade, Susana; Giacosa, Simone; Cocolin, Luca; Paissoni, Maria Alessandra; Lambri, Milena; Rantsiou, Kalliopi; Maury, Chantal
Graphical abstract: Highlights: Electrolyzed water preharvest grape treatments were tested to evaluate TCA occurrence in wine. The EW treatments influenced the indigenous yeast populations of grape surface. EW preharvest grape treatments resulted in TCA presence after fermentation. Chlorophenols and TCA contents was mitigated after wine storage. Abstract: Recently the use of electrolyzed water (EW) attracted much attention as a high-performance, new technology for its potential use in the food industry. The aim of this work was to investigate the impact of grape EW treatments, applied at different time intervals prior to harvest, on the indigenous yeast populations of grape surface (Chenin blanc and Cabernet franc) and the occurrence of 2, 4, 6-trichloroanisole (TCA) in Cabernet franc wine. In addition, the evolution of inoculated and spontaneous fermentations on treated and non-treated grapes was also considered. The yeast population present on grape berries surface was influenced in a grape variety and EW treatment time-dependent way, since only Chenin blanc grapes treated with EW 7 days prior to harvest had significantly lower yeast population levels, compared to the respective control. Concerning the yeast diversity in the grape samples, a dominance of Aureobasidium pullulans was observed in treated grapes, independently of the grape variety. At the end of alcoholic fermentation, 2, 4, 6-trichloroanisole was detected in wine when the EW solution was applied at one or two weeks before harvest time. After wine storage, 2, 4, 6-trichloroanisole and chlorophenols contents generally exhibited a loss relative to initial values. The results showed that EW treatments tended to slightly increase the TCA concentration in final wine and did not affect the fermentation performances and chromatic properties of resulting wine. On the other hand, absorption or desorption phenomena by wine lees could be involved in the change of 2, 4, 6-trichloroanisole concentration in wine during storage time.